The Contribution of Mohammad Natsir's Thoughts in The Formation of The Unitary State of The Republic of Indonesia (NKRI) Perspective of Religious Moderation Da'wah - Ali Abdurrahim (CV. Syntax Corporation Indonesia, 2023)
This research is qualitative in nature which produces descriptive data. This research is a type of library research, which is conducting research by studying and reading literature that has to do with the problem that is the object of research. This type of research is included in the explanatory, which is looking for new things from historical facts in the form of the application of Mohammad Natsir's da'wah thought to then be formulated analytically as a strategy pattern in religious moderation da'wah using descriptive analysis methods. This technique begins with reducing data, then organizing and explaining, verifying then ending with impending data on